Quelques éléments sur les implications de la stratégie maritime américaine en Europe - Santos, Alberto (Études internationales, 1987)
It is generally accepted that maritime strategy, which has never ceased to be one of the main concerns of the American strategists since 1898, has contributed significantly to the changes which have occurred in strategic thought since 1981, and that it has an influence on the evolution of the Atlantic Alliance. In this study, an attempt is made to full the gaps in the thoughts on US maritime strategy by focussing on an analysis of the debate as revived by the 1982 war in the Malvinas although such debate was current under the Carter administration; a debate which has attracted very little attention, if any, from those who have been studying the question of expenditures in Europe. It opposes two of the main schools of thought in strategy, namely the maritimist and the coalitionist.